Examining the Validity of AHRQ's Patient Safety Indicators (PSIs): Is Variation in PSI Composite Score Related to Hospital Organizational Factors?. (December 2014) - Shin, Marlena H.; Sullivan, Jennifer L.; Rosen, Amy K.; Solomon, Jeffrey L.; Dunn, Edward J.; Shimada, Stephanie L.; Hayes, Jennifer; Rivard, Peter E.
Increasing use of Agency for Healthcare Research and Quality's Patient Safety Indicators (PSIs) for hospital performance measurement intensifies the need to critically assess their validity. Our study examined the extent to which variation in PSI composite score is related to differences in hospital organizational structures or processes (i.e., criterion validity). In site visits to three Veterans Health Administration hospitals with high and three with low PSI composite scores ("low performers" and "high performers, " respectively), we interviewed a cross-section of hospital staff. We then coded interview transcripts for evidence in 13 safety-related domains and assessed variation across high and low performers. Evidence of leadership and coordination of work/communication (organizational process domains) was predominantly favorable for high performers only. Evidence in the other domains was either mixed, or there were insufficient data to rate the domains. While we found some evidence of criterion validity, the extent to which variation in PSI rates is related to differences in hospitals' organizational structures/processes needs further study.